Eco-physiology and mesocosm study on microalgae in oligotrophic and mesotrophic municipal manmade lakes in different weather conditions - Alteerah, Munay Abdulqadir Omar Abdulqadir (2017)
Numerous weather records from all over the world indicated that climate changes are happening including in Malaysia. Climate change influences daily weather conditions and the biotic component in water bodies. Unlike the subtropics and temperate regions, Malaysia has no distinct seasons. Most studies are on microalgae diversity and water quality parameters but few studies were available on the impact of changing weather conditions on microalgae species composition, diversity and productivity. Therefore the objectives of this study are to evaluate the effect of variable weather conditions on water quality, diversity, succession of microalgae, primary productivity of the mix microalgae in two urban manmade lakes and mixed microalgae study in floating mesocosms. Daily weather conditions monitored three times daily at morning (8.0-9.0), noon (12.0-13.0) and afternoon (16.0-17.0). The weather is classified into mix, wet and dry conditions based on weather scoring. Lake study comprised of weekly sampling for 22 weeks was carried out for water physico-chemical parameters, microalgae species composition and diversity, microalgae biomass and productivity. A set of mesocosms outdoor experiment was performed to evaluate the productivity of mix microalgae in semi controlled conditions with sampling every two days. Mesocosms were divided into four treatments: non-sheltered with fertilizer, non-sheltered without fertilizers, sheltered with fertilizers, sheltered without fertilizers. Triple supper phosphates and urea (2g: 20 g) were used as fertilizers. Statistical analysis were done using one way ANOVA, Canonical corresponding analysis (CCA), Principal Component Analysis (PCA) and Factorial ANOVA for microalgae culture parameters. The mean water quality parameters of the lake during all weather conditions were: water temperature (28.95 & 29.43 ̊C), pH (7.14 & 7.11), electrical conductivity (0.15 & 0.41 mS/cm), dissolved oxygen (5.5 & 4.5mg/L), alkalinity (43.8 & 148.2 mgCaCO3/L), orthophosphates (0.02 & 0.42 mg / L), nitrate-nitrogen (0.2 & 0.07 mg/L), ammonium-nitrogen (0.06 & 0.96 mg/L), trophic status index (20.6 & 37.5) in Engineering lake and Seri Serdang Lake respectively. A total of 65 species from five divisions (Chlorophyta, Euglenophyta, Cyanophyta, Bacillariophyta and Dinophyta) and 51 species belonging to six divisions (Chlorophyta, Cyanophyta, Bacillariophyta, Euglenophyta, Cryptophyta & Charophyta) were recorded from Engineering Lake and Seri Serdang Lake respectively. Division Chlorophyta was the most dominant in Engineering Lake comprising of 67.6% and in Seri Serdang lakes comprising of 67.3%during all sampling weeks. In dry weather conditions, the microalgae density was low in both lakes. Engineering lake and Seri Serdang Lake showed the highest means chlorophyll a concentration of 0.65±0.028 & 4.83±0.96 μg/L respectively in dry weather conditions. Engineering lake and Seri Serdang Lake also showed highest mean of temporal fluctuations of primary production with 0.43±0.03 & 2.14 ± 0.85 mg C/ L/ h respectively. Reduction of light intensity during mix weather conditions was the main factor behind the reduction of primary productivity in both lakes. Increase light intensity and nutrient concentration during dry weather conditions led to improve microalgae primary productivity. Small mesotrophic manmade lake (Seri Serdang) showed its importance in producing O2and CO2sequestration. Weather conditions inmesocosms study period were scored and categorized to ensure each cultivation cycle was under one type of weather conditions. Water quality parameters in all treatmentscultures was monitored for 10 days in three cycles and showed significant variations among the variables. Nutrients decreased during cultivation period and the growth performance of the mix microalgae in fertilized and non-fertilized mesocosms from three culture cycles slightly increased with culture time. Primary productivity was higher in the fertilized non-sheltered mesocosms (Treatment 1). On the 10thday of culture primary productivity in treatment 1, 2, 3 & 4 were lower in the dry cycle (0.7±0.1) (0.2±0.0) (0.2±0.0) (0.5±0.0) g/l dry wt and higher in the mix cycle (2.2±0.3)(0.4±0.0) (0.7±0.5) (0.4±0.0) respectively. In different mesocosms treatment, the diversity of microalgae did not differ much. Twenty-six species were recorded in mixed and wet cycle and twenty-nine dry cycles. Chlorophyta due to its versatile adaptability was the main dominant group during all cycles comprising 80%, 83%, and 85% during mix, dry and wet cycles respectively. Different weather conditions and different treatments including sheltered & non- sheltered significantly influenced microalgae species composition. This was probably due to the sensitivity in some of them to different light intensities. This study concluded that light intensity, and temperature were the main factors that can impact microalgae growth and morphological features. Malaysian weather conditions are variable that can be categorized as wet, mixed and dry. The weather conditions exert its influence on water physico-chemical water parameter, microalgae diversity and productivity. Mesocosms study also confirmed the findings in oligotrophic and mesotrophic lake on the impact of weather condition on water quality parameters, microalgae diversity and productivity.